PROCEDURAL STATUS OF A LAWYER IN THE RECOVERY OF MATERIAL DAMAGES IN COURTS OF STATE AND NATURAL MONUMENTS - Shoymardonov Botir Norkeldievich (Western European Studies, 2024)
This article explores the procedural status of a lawyer in the recovery of material damages in courts of state and natural monuments. It analyzes the role and responsibilities of lawyers in representing clients seeking compensation for damages to state and natural monuments, including navigating the legal system, presenting evidence, and advocating on behalf of their clients. The article also discusses the challenges and opportunities that lawyers face in this specialized area of law.
Keywords: Lawyer; procedural status; recovery; material damages